Handouts: a tool for teacher teaching practices to adjust students’ scriptural skills and the content being taught. - Khaneboubi, Mehdi; Roux-Goupille, Camille (Swiss Journal of Educational Research, 2020)
Discourse analyses of 46 teachers from general, technological and professional high schools makes us consider the use of handouts as an adaptation of the content taught to the reading and writing skills of students. Students’ scriptural skills influence teachers’ teaching strategies and the nature of handouts. Depending on whether they consider that their students need to practice in reading or writing, they design different documents fitted to their needs. When students are good readers, the printed media becomes invisible and the teaching and design strategy for the handout is focused on content only.